2022 IEEE International Conference on Big Data (Big Data) 2022
DOI: 10.1109/bigdata55660.2022.10020259
|View full text |Cite
|
Sign up to set email alerts
|

A Data-driven Latent Semantic Analysis for Automatic Text Summarization using LDA Topic Modelling

Abstract: With the advent and popularity of big data mining and huge text analysis in modern times, automated text summarization became prominent for extracting and retrieving important information from documents. This research investigates aspects of automatic text summarization from the perspectives of single and multiple documents. Summarization is a task of condensing huge text articles into short, summarized versions. The text is reduced in size for summarization purpose but preserving key vital information and ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Several studies have also demonstrated the viability of a topic modeling approach on extractive summarization [14]- [16]. Those studies incorporated bag-of-words approach-based algorithms, such as latent dirichlet allocation (LDA) and latent semantic analysis (LSA).…”
Section: Related Work 21 Topic Modelingmentioning
confidence: 99%
“…Several studies have also demonstrated the viability of a topic modeling approach on extractive summarization [14]- [16]. Those studies incorporated bag-of-words approach-based algorithms, such as latent dirichlet allocation (LDA) and latent semantic analysis (LSA).…”
Section: Related Work 21 Topic Modelingmentioning
confidence: 99%
“…The analyst should find the optimal interpretation by changing lambda to a value between 0 and 1. If lambda is close to 0, the characteristics of the subject are emphasized, but unnecessary junk words may also be extracted; if lambda is close to 1, words that reveal the characteristics of the subject may not appear [29].…”
Section: Modelingmentioning
confidence: 99%
“…LDA also facilitates abstraction through topic summarisation. LDA generates a set of word-topic distributions representing the probability of each word occurring in each topic (Onah et al, 2022). Through examining the most probable words that are associated within each topic, researchers can gain an understanding of the main concepts and themes that are represented by the topics.…”
Section: Introductionmentioning
confidence: 99%
“…Through examining the most probable words that are associated within each topic, researchers can gain an understanding of the main concepts and themes that are represented by the topics. This summarisation aids in distilling key information and abstracting the data (Onah et al, 2022). This then helps to accomplish a key outcome sought throughout an SLR; the identification of gaps in the research domain under investigation through a comprehensive summary of its pertinent research (Paul et al, 2021).…”
Section: Introductionmentioning
confidence: 99%